Impact of Use of Ultrasound-Assisted Extraction on the Quality of Brazil Nut Oil (Bertholletia excelsa HBK) - Orquidea Vasconcelos dos Santos; Sara Camila Vidal Freires; Helen Cristina de Oliveira Palheta; Paulo Henrique de Melo Ferreira (Separations, 2025)
The quality of materials extracted from plant sources, such as oilseeds, is significantly affected by the extraction techniques employed. Thermo-photosensitive bioactive compounds are especially susceptible, often resulting in a loss of functional properties during conventional processing. In this context, studies involving unconventional or “innovative” extraction methods have emerged as a strategic approach to preserve the quality of the extracted material (whether by-product or biomass) by aligning with the core principles of green chemistry and the expansion of sustainable production chains. This approach promotes both raw material integrity and the protection of human and environmental health. These efforts contribute to a virtuous cycle of technological innovation and environmentally sound practices. This review focuses on how ultrasound-assisted extraction affects the quality of plant-derived materials, particularly Brazil nut oil. The article compiles data published over the last five years (2020–2025), following the PRISMA methodology. Recent studies highlight the synergistic potential of ultrasound as a green technology for isolating Brazil nut oil, offering enhanced nutritional and functional properties. This aligns with the growing demand for healthier food products obtained through sustainable industrial processes and presents opportunities for diverse applications across several industry sectors.